The Influence Of Work Discipline And Work Environment On Employee Performance In Regional Public Water Companies - Selvi Pebriyanti; Budi Rismayadi; Wike Pertiwi (PT. Berkah Digital Teknologi, 2025)
Purpose of the study — This study aims to examine the effect of work discipline and work environment on employee performance. Research method—The research employs a quantitative approach using verification analysis, conducted at Perumdam Tirta Tarum Karawang. The population consisted of 343 employees, with a sample of 78 determined using the 10% Solvin formula. Data analysis was performed using multiple linear regression with the SPSS 27 application. Result— The findings indicate a significant influence of work discipline on employee performance, evidenced by ttabel (2.295 > 2.011 or thitung > ttabel). Additionally, the work environment also significantly affects employee performance, with ttabel (8.224 > 2.011). Conclusion— Both work discipline and work environment significantly influence employee performance at Perumdam Tirta Tarum Karawang.